A Structured Approach to Assessing Clinical Competence in Conservative Dentistry: A Checklist-Based Evaluation for Dental Students performing Class I Composite Restorations - Elhenshiri, Khaled; Mohamed Benhakoma; Fatma Soltan; Asma Abognah; Farida Alsayeh (AlQalam Journal of Medical and Applied Sciences, 2025)
Accurate evaluation of clinical competence in restorative dentistry requires reliable assessment tools. Checklists - based standardized tool has the potential to enhance objectivity, but not full representation of students’ underlying knowledge. This study aimed to validate a structured checklist for Class I composite restorations by examining inter-examiner reliability and comparing it with novice students’ self-assessment accuracy. The cross-sectional study involved thirty undergraduate dental students. Each student performed a standardized Class I composite restoration, assessed concurrently by three independent faculty examiners and through student self-evaluation using the same instrument. Internal consistency, Cronbach’s (α), inter-examiner reliability (ICC), and Pearson correlation (r) were used for analysis. The checklist showed good internal consistency (α = 0.83) and moderate agreement amongst examiners (ICC = 0.60). The mean score for student self-assessment (33.6) was slightly higher than the mean score for examiner assessments (32.7), but their relationship was negligible and negative (r = -0.06, p = 0.75). Significantly, including the self-assessment scores reduced the overall reliability of the scale, with the ICC dropping sharply to 0.30, indicating low correspondence. The developed checklist proves to be a reliable and objective measure for clinical assessment. These findings, however, emphasize a critical need for enhanced examiner calibration and integration of formal reflective practice training to improve students’ self-assessment accuracy and professional self-awareness.